The use of medicinal plants in the Aneuk Jamee tribe in Kota Bahagia, South Aceh District, Indonesia - NURSAMSU NURSAMSU; NURAINI NURAINI; TRI MUSTIKA SARJANI; MARDUDI MARDUDI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Nursamsu, Nuraini, Sarjani TM, Mardudi. 2024. The use of medicinal plants in the Aneuk Jamee tribe in Kota Bahagia, South Aceh District, Indonesia. Biodiversitas 25: 2524-2540. The Aneuk Jamee tribe comes from the Acehnese language, namely "Aneuk" which means child, while "Jamee" means guest/immigrant who is in the south of Aceh. The development of the use of medicinal plants is very promising in terms of supporting factors such as the availability of rich and diverse biological resources which can be developed as alternative treatment options for various types of diseases. The aim of this research is to document and study further the medicinal plants used by the Aneuk Jamee tribe in Kota Bahagia Sub-Sub-district, South Aceh, Indonesia, in four villages, namely Jombo Keupok, Alur Dua Mas, Ujong Tanoh and Beutong. This research is based on field surveys, plant collections, and interviews with local people. Interviews were conducted with 11 key respondents who are experts in the field of local medicine who were selected using the purposive snowball sampling method. This research highlights around 152 plant taxa belonging to 59 families. Poaceae (13 taxa) are the dominant family of medicinal plants. In the medicinal plant habitat, 77 taxa (50.7%) are predominantly wild and 75 taxa (49.3%) are cultivated. The part of the plant that is commonly used is the leaves (46.1%) which is the dominant part used. Squeezing (24%) was the main preparation method, and drinking (60.4%) was the commonly used method. The study categorizes 59 diseases into 16 categories. A high Informant Consensus Factor (ICF) value indicates that symptoms and signs affecting the skin and subcutaneous tissue (SCT), as well as diseases related to the blood and blood-forming organs, including certain disorders involving the body's immune mechanisms (DBF), have a significant level of agreement among the informants.